Male age and strain affect ejaculate quality in the Mexican fruit fly - Herrera Cruz, Mariana (2017)
Aging in all organisms is inevitable. Male age can have profound effects on mating success and female reproduction, yet relatively little is known on the effects of male age on different components of the ejaculate. Furthermore, in mass-reared insects used for the Sterile Insect Technique, there are often behavioral differences between mass-reared and wild males, while differences in the ejaculate have been less studied. The ejaculate in insects is composed mainly of sperm and accessory gland proteins. Here, we studied how male age and strain affected (i) protein quantity of testes and accessory glands, (ii) the biological activity of accessory gland products injected into females, (iii) sperm viability, and (iv) sperm quantity stored by females in wild and mass-reared Anastrepha ludens (Diptera: Tephritidae). We found lower protein content in testes of old wild males and lower sperm viability in females mated with old wild males. Females stored more sperm when mated to young wild males than with young mass-reared males. Accessory gland injections of old or young males did not inhibit female remating. Knowledge of how male age affects different ejaculate components will aid our understanding on investment of the ejaculate and possible postcopulatory consequences on female behavior.